Low-field and high-field magnetic resonance contrast imaging of magnetoferritin as a pathological model system of iron accumulation. (21st August 2017) - Strbak, Oliver; Balejcikova, Lucia; Baciak, Ladislav; Kovac, Jozef; Masarova-Kozelova, Marta; Krafcik, Andrej; Dobrota, Dusan; Kopcansky, Peter
Abstract: Various pathological processes including neurodegenerative disorders are associated with the accumulation of iron, while it is believed that a precursor of iron accumulation is ferritin. Physiological ferritin is due to low relaxivity, which results in only weak detection by magnetic resonance imaging (MRI) techniques. On the other hand, pathological ferritin is associated with disrupted iron homeostasis and structural changes in the mineral core, and should increase the hypointensive artefacts in MRI. On the basis of recent findings in respect to the pathological ferritin structure, we prepared the magnetoferritin particles as a possible pathological ferritin model system. The particles were characterised with dynamic light scattering, as well as with superconducting quantum interference device measurements. With the help of low-field (0.2 T) and high-field (4.7 T) MRI standard T 2 -weighted protocols we found that it is possible to clearly distinguish between native ferritin as a physiological model system, and magnetoferritin as a pathological model system. Surprisingly, the T 2 -weighted short TI inversion recovery protocol at low-field system showed the optimum contrast differentiation. Such findings are highly promising for exploiting the use of iron accumulation as a noninvasive diagnostics tool of pathological processes, where the magnetoferritin particles could be utilised as MRI iron quantification calibration samples.